Get on the job and organize : standing up for a better workplace and a better world - Brisack, Jaz (One Signal Publishers, Atria, 2025)
"Get on the Job and Organize is a compelling, inspirational narrative of the Starbucks and Tesla unionization efforts, telling the broader story of the new, nationwide labor movement unfolding in our era of political and social unrest. As one of the exciting new faces of the American Labor Movement, Jaz Brisack argues that while workers often organize when their place of work is toxic, it's equally important to organize when you love your job. With an accessible voice and profound insight, Brisack puts everything into the context of America's long tradition of labor organizing and shows us how we too can organize our workplaces, from how to educate yourself and your colleagues, to what backlash can be expected and how to fight it, to what victory looks like even if the union doesn't necessarily 'win.'"--